Jurnal Rancang Bangun Media Pembelajaran Ilmu Nahwu Berbasis Website: Studi Kasus : Pesantren Al Bukhori Brebes - Muhammad Ahsan Jamil; Rosidin Rosidin; Sukarsa Sukarsa; Dicky Andika Sulaeman; Akhmad Purnamaysah (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
The 21st century is characterized by rapid advancements in information technology, impacting various aspects of life, including education systems. In this context, educational media plays a crucial role in enhancing the effectiveness of communication between educators and learners. Pesantren Al Bukhori, an Islamic educational institution in Brebes Regency, still relies on conventional methods for teaching Ilmu Nahwu, which limits learning within specific spaces and times. This research, titled "Design and Development of a Web-Based Educational Media for Ilmu Nahwu (Case Study: Pesantren Al Bukhori Brebes)," aims to design and build a web-based educational media that allows for more flexible interactions between students and teachers and expands the scope of learning at Pesantren Al Bukhori. The research employs the waterfall method, including stages of needs analysis, design, implementation, testing, and maintenance. Feasibility testing was conducted using the WebQual instrument to evaluate the website's quality from the user's perspective. The results showed that the website was tested using a Likert Scale and received an interval score of 78,43% from 16 respondents. This score indicates that the website falls into the "good" or "satisfactory" category, demonstrating that the web-based educational media is effective in enhancing the teaching and learning process of Ilmu Nahwu.